Impact of Thunderstorm Activities on Tropospheric NOx Over Koshi Province of Nepal and Their Possible Role in Climate Change - Ghimire, Ram Chandra; Sharma, Shriram; Neupane, Sujan (Amrit Research Journal, 2024)
Lightning, a natural atmospheric phenomenon, plays a significant role in altering atmospheric chemistry and air quality by generating nitrogen oxides (NOX). This research aims to explore the correlation between lightning stroke density and atmospheric NOX over Koshi Province of Nepal by using observational data. Over the course of three year (2018, 2019 and 2020), sessional (lightning pre-dominant; pre-monsoon and post-monsoon) measurements of lightning activity (lightning stroke density) were obtained from Global Lightning Dataset (GLD 360) and NOX data acquired from NASA’s Ozone Monitoring Instrument (OMI). The computation was conducted by using programming language PYTHON. Correlation analysis was performed to examine the relationship between lightning stroke density and NOX concentrations by considering lightning stroke density as independent variable and average NOX as dependent variable. Our analysis shows a notable positive correlation between lightning stroke density and average NOX over Koshi Province of Nepal. The values of correlation coefficient (R) was found 0.625, 0.630 and 0.511 in pre-monsoon of years 2018, 2019 and 20120 respectively and 0.654, 0.605 and 0.370 respectively in post-monsoon. Increased lightning activity corresponded to heightened NOX concentrations, especially during pre-monsoon and post-monsoon. These results indicate that lightning significantly contributes to NOX emissions in Koshi Province. Understanding the relationship between lightning and NOX is essential for study atmospheric chemistry and assessing the impact of lightning on atmosphere.